The Influence of Work Environment and Job Promotion on Employee Performance Through Organizational Commitment at Raden Mattaher Regional General Hospital, Jambi Province - Irzani, Irzani; Suryani, Arna; Akbar, Ali (DINASTI RESEARCH, 2025)
This study aims to identify and describe the work environment, job promotion, organizational commitment, and employee performance at Raden Mattaher Regional General Hospital, Jambi Province, as well as to examine and analyze the influence of the work environment and job promotion on employee performance through organizational commitment. The research adopts a descriptive-verificative design and employs Partial Least Squares (PLS) analysis. The descriptive analysis concluded that the work environment is categorized as “Good,” and job promotion also falls into the “Good” category. Furthermore, the organizational commitment variable is classified as “High,” and the employee performance variable is also categorized as “High.” The results of the PLS analysis show that the work environment and job promotion have a positive and significant effect on organizational commitment. Additionally, both the work environment and job promotion have a positive and significant effect on employee performance through organizational commitment at Raden Mattaher Regional General Hospital, Jambi Province.